2020
DOI: 10.1002/jmv.26235
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 3 as a valuable marker for patients with COVID‐19

Abstract: The situation of the coronavirus disease 2019 (COVID‐19) continues to evolve, our study explored the significance of serum levels of matrix metalloproteinase 3 (MMP3) as a marker for patients with COVID‐19. Sixty‐two COVID‐19 patients in the First Hospital of Hunan University of Chinese Medicine and Loudi Center for Diseases Prevention and Control, from January to March 2020, were sampled as the novel coronavirus pneumonia infected group. One hundred and thirty‐one cases from the First Hospital of Hunan Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 19 publications
0
37
1
Order By: Relevance
“…In particular, we found the upregulation of CXCL8 , CXCL10 , CCL2 , MMP3 , CCL5 , and PTGS2 encoding for IL-8, IP-10, MCP-1, MMP3, RANTES and COX2, respectively ( Table 2 ). IL-8, IP-10, MCP-1 and MMP-3 serum levels were suggested as biomarkers for COVID-19 disease [ 73 , 74 , 75 ]. RANTES and COX-2 increased in SARS-CoV-2 infection [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, we found the upregulation of CXCL8 , CXCL10 , CCL2 , MMP3 , CCL5 , and PTGS2 encoding for IL-8, IP-10, MCP-1, MMP3, RANTES and COX2, respectively ( Table 2 ). IL-8, IP-10, MCP-1 and MMP-3 serum levels were suggested as biomarkers for COVID-19 disease [ 73 , 74 , 75 ]. RANTES and COX-2 increased in SARS-CoV-2 infection [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are discharged during lung inflammation in the extracellular matrix that leads to elevated chemokines with inflammatory properties ( 30 ). Published studies clearly demonstrated that MMP-3 and MMP-9 were significantly elevated and also act as immune markers for inflammation in patients with COVID-19 ( 31 , 32 ). In this study, we demonstrate that almost all the estimated MMPs, MMP-1, MMP-2, MMP-3, MMP-7, MMP-8, MMP-9, MMP-12, and MMP-13, were significantly down-regulated at 1 month after vaccination when compared to baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Neither COVID-19 nor DENV disease has been shown to cause coronary artery ectasia (CAE). Degradation of the medial arterial layer by activation of serine proteinase in addition to matrix metalloproteinase (MMP) in the arterial smooth muscle cells generates CAE [ 38 ]; a study by Shi et al [ 39 ] measured the levels of matrix metalloproteinase 3 in serum, comparing noninfected and infected patients with COVID-19, and found a significant difference in serum MMP3. Patients with COVID-19 have an increase in this enzyme, although a laboratory analysis of MMP3 in this case report was not available.…”
Section: Discussionmentioning
confidence: 99%